Cortico-cortical activity between the primary and supplementary motor cortex: An intraoperative near-infrared spectroscopy study - Fukuda, Masafumi (Surg Neurol Int, 2015)
BACKGROUND: The supplementary motor area (SMA) makes multiple reciprocal connections to many areas of the cerebral cortices, such as the primary motor cortex (PMC), anterior cingulate cortex, and various regions in the parietal somatosensory cortex. In patients with SMA seizures, epileptic discharges from the SMA rapidly propagate to the PMC. We sought to determine whether near-infrared spectroscopy (NIRS) is able to intraoperatively display hemodynamic changes in epileptic network activities between the SMA and the PMC. CASE DESCRIPTIONS: In a 60-year-old male with SMA seizures, we intraoperatively delivered a 500 Hz, 5-train stimulation to the medial cortical surface and measured the resulting hemodynamic changes in the PMC by calculating the oxyhemoglobin (HbO2) and deoxyhemoglobin (HbR) concentration changes during stimulation. No hemodynamic changes in the lateral cortex were observed during stimulation of the medial surface corresponding to the foot motor areas. In contrast, both HbO2 and HbR increased in the lateral cortex corresponding to the hand motor areas when the seizure onset zone was stimulated. In the premotor cortex and the lateral cortex corresponding to the trunk motor areas, hemodynamic changes showed a pattern of increased HbO2 with decreased HbR. CONCLUSIONS: This is the first reported study using intraoperative NIRS to characterize the epileptic network activities between the SMA and PMC. Our intraoperative NIRS procedure may thus be useful in monitoring the activities of cortico-cortical neural pathways such as the language system.